Efficacy and safety of intermittent fasting for type 2 diabetes mellitus: A systematic review and meta-analysis of randomized trials - Joshua Chadwick; Lavanya Ayyasamy; Madhanraj Kalyanasundaram; Ganeshkumar Parasuraman; Bhavani Shankara Bagepally; Jeyashree Kathiresan; Lokesh Shanmugam (Diabetes Epidemiology and Management)
Background & objectives: Type 2 diabetes mellitus (T2DM) is a pressing public health concern, contributing to 11 % of annual deaths and incurring direct expenses of $760 billion. Studies show intermittent fasting (IF) can effectively lower glycated haemoglobin (HbA1c) levels and reduce weight and levels in individuals with type 2 diabetes. The study's objective is to evaluate the efficacy and safety of IF on glycaemic control among patients with T2DM. Methods: We conducted searches in the MEDLINE (Ovid), Embase, and SINOMED databases until February 29, 2024, focusing on glycaemic control as the outcome of interest. Secondary outcomes included changes in weight, and BMI (PROSPERO ID: CRD42022357598). We used a random effect model to synthesize the effect measure. We performed a sensitivity analysis to assess the robustness of the result. Results: Out of the 24 studies identified, nine were deemed suitable for inclusion. Four studies, including 238 participants, were selected for the meta-analysis. The analysis revealed that IF and regular diets showed similar effects on glycemic control, HbA1c (−1.27 %, 95 % confidence interval [CI] −3.71 to 1.17) and fasting plasma glucose (−1.66, 95 % CI −4.22 to 0.90). Weight reduction outcomes were also similar between the two diets (−0.26, 95 % CI −1.43 to 0.91 kg). The frequency of hypoglycemic episodes was comparable across both groups. Interpretation & conclusions: On the basis of moderate to low certainty of evidence, IF can be a safe dietary approach for patients with T2DM, with similar safety and effectiveness profiles to regular diets. However, larger-scale studies are recommended to confirm these findings.